In Defense of Doctors Who Treat Pain – Questions and Answers for Judges, Juries… and Journalists – - A Lawhern PhD, Richard (Clinical Medicine And Health Research Journal, 2024)
As a healthcare writer and patient advocate for almost 30 years, I read a lot. Recently, some of that reading has been in court transcripts of doctors being persecuted out of medicine or into jail by DEA prosecutors and their hired “experts.” I use the term “persecuted” intentionally. I believe that many DEA or State Attorney General “medical experts” are simply “hired guns” – clinical predators paid large sums of money to tell stories whose details they do not actually understand.